Peroperative evaluation of vascularity of various flaps by fluorescein technique - Bhattacharya, V; Sunish, Goyal; Nepram, Sanjib Singh; Manihar, H Singh; Sheikh, Adil Bashir (Indian Journal of Plastic Surgery, 2006)
Background: The viability of any pedicled flap depends upon its vascularity. When a flap is dissected it becomes relatively ischaemic. Ultimately, the viability of the flap depends on the vessels incorporated in the pedicle and their perfusion capacity. There are different techniques to evaluate the blood supply of a flap.Aims: This study deals with experimental and clinical efficiency of fluorescein dye technique to evaluate the vascularity of flaps of various compositions.Materials and Methods: The experimental study was conducted on rats to standardize the technique. Thereafter clinical evaluation was conducted for different flaps namely fasciocutaneous, skeletonized perforator based fasciocutaneous, adipofascial, fasciocutaneous flap with adipofascial extension, fasciocutaneous flap with fascial extension and fasciocutaneous flap with split fascial extension.Conclusions: The paper deals in detail with the technique and method of documentation of a fluorescein study on flaps both experimentally and clinically. The appearance of fluorescein on both the surfaces and distal margin of the flap confirmed the adequacy of vascularity soon after dissection of the flaps. It was found to be an easy, safe and reliable objective method.
Keywords: Peroperative fluorescein dye study; vascularity; flaps